Analisis ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN NIAT PEMBELIAN ULANG MINUMAN KOPI GEROBAK LISTRIK MENGGUNAKAN TEORI PERILAKU TERENCANA - Suparman, Yusuf Fauzi; Tanding Suryandari, Retno (Universitas Muhammadiyah Pontianak, 2026)
This study examines factors influencing repurchase intention of electric cart coffee beverages using the Theory of Planned Behavior (TPB). A survey of 230 university students in Yogyakarta was conducted and analyzed using SEM-PLS. Results show that perceived quality and price significantly affect attitude, subjective norms, and perceived behavioral control. Attitude, subjective norms, and perceived behavioral control significantly influence repurchase intention. Perceived quality has a direct significant effect, while price does not. These findings underscore the importance of quality and psychological drivers in forming repurchase intention in the mobile coffee context. Keywords: Theory of Planned Behavior, Perceived Quality, Price, Attitude, Subjective Norms, Perceived Behavioral Control, Repurchase Intention, Electric Cart Coffee